Adverse reactions to inactivated COVID-19 vaccination in patients with chronic liver disease: The effect of anxiety. Issue 6 (30th November 2022) - Lv, Li; Lin, Xiao-Qing; Chen, Yan; Chen, He-Dan; Zhang, Mei-Xian; Shao, Hui; Tung, Tao-Hsin; Zhu, Jian-Sheng
ABSTRACT: Studies have shown that patients with chronic liver disease are at a higher risk of contracting novel coronavirus pneumonia than healthy individuals, and many guidelines state that patients with chronic liver disease should be prioritized for COVID-19 vaccination, but there are a few studies on its safety in CLD patients. We aimed to evaluate the safety of the inactivated COVID-19 vaccine in patients with chronic liver disease, and the effect of anxiety on adverse reactions. A questionnaire survey for self-administered post-vaccination adverse reaction monitoring was conducted from June 17, 2021, to August 11, 2021, in patients with chronic liver disease attending a tertiary care hospital in Taizhou, China. We analyzed the data from of a total of 160 participants who scanned the QR code on social media to respond to the questionnaire. The overall incidence of adverse reactions after COVID-19 vaccination in patients with chronic liver disease was 44.4% (71/160), and the most common adverse reaction was local injection site reaction, accounting for 80.3% of adverse reactions (57/71). No serious adverse reactions were reported. Approximately 53.1% of the patients had anxiety about vaccination, and 51.8% of those who felt anxious reported adverse reactions. The safety of COVID-19 vaccination in patients with chronic liver disease is good, and there is a strong association between adverse reactions and vaccine anxiety. Pre-vaccination education for patients with vaccine anxiety and psychological counseling may reduce reports of adverse reactions and improve patients' confidence in the vaccine.